Es kādreiz dziedāju korī «Juventus» - Tomsone, Paula (My University, 2020)
Virtuālā izstāde "Es kādreiz dziedāju korī "Juventus"" veltīta Latvijas Universitātes jauktā kora "Juventus" 100 dibināšanas jubilejai. Izstāde sniedz informāciju par kora vēsturi un izveidošanos, zināmākajiem diriģentiem, tradīcijām un koncertiem Latvijā un ārpus tām. Izstāde apskatāmas fotogrāfijas un vēsturiskas liecības, kas glabājas LU Muzejā, par kora darbību.

The virtual exhibition "I used to sing in the choir" Juventus "" is dedicated to the 100th anniversary of the founding of the mixed choir "Juventus" of the University of Latvia. The exhibition provides information about the history and formation of the choir, the most famous conductors, traditions and concerts in Latvia and abroad. The exhibition includes photographs and historical evidence stored in the Museum of the University of Latvia about the choir's activities.
Latvijas Universitātes kora «Juventus» vēstures liecības LU Muzeja krājumā
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects; Pašdarbība - Latvijas Universitāte; Latvijas Universitātes koris «Juventus»; Latvijas Universitāte - vēsture